Improving Undergraduate Medical Education about Pain Assessment and Management: A Qualitative Descriptive Study of Stakeholders’ Perceptions - Pierre-Paul Tellier; Emmanuelle Bélanger; Charo Rodríguez; Mark A Ware; Nancy Posel (Pain Research and Management)
BACKGROUND: Pain is one of the most common reasons for individuals to seek medical advice, yet it remains poorly managed. One of the main reasons that poor pain management persists is the lack of adequate knowledge and skills of practicing clinicians, which stems from a perceived lack of pain education during the training of undergraduate medical students.